(untitled) (NTU Journal of Agriculture and Veterinary Science, 2025)
Wheat straws were pyrolyzed at 200°C, 400°C, and 600°C to create biochar. Experiments on biochar incubation with calcareous soil were carried out at 1, 2, 4, 6, and 8 g kg?1 for a maximum of 60 and 90 days at rates to silty loam. The soil’s pH, EC, and CEC values were measured, in addition to its accessible N, P, and K. The availability of pH, EC, CEC, N, P, and K increased with the usage of biochar. The pH values ranged from 7.35 at 200°C for 60 days to 7.94 at 600°C for 90 days, while the electrical conductivity increased from 2.42(dS.m-1) at 200°C for 60 days to 4.65(dS.m-1) at 600°C for 90 days, and the cation exchange capacity values increased from 14.35 (Cmol. Kg -1)at 200°C for 60 days to 22.37 (Cmol. Kg -1)at 600°C for 90 days. Moreover, a significant increase in the availability of nutrients (N, P, and K) was observed, reaching 83(mg.Kg-1) at 200°C for 60 days to 107 (mg.Kg-1) at 600°C for 90 days, 34 (mg.Kg-1) at 200°C for 60 days to 54 (mg.Kg-1)at 600°C for 90 days,113 (mg.Kg-1) at 200°C for 60 days to 135 (mg.Kg-1)at 600°C for 90 day respectively. It was found that the correlation coefficient between soil properties with biochar levels ,temperature and Incubation period time for all soils was high and positive.